Expanding the apelin receptor pharmacological toolbox using novel fluorescent ligands - Williams, Thomas L.; Macrae, Robyn G. C.; Kuc, Rhoda E.; Brown, Alastair J. H.; Maguire, Janet J.; Davenport, Anthony P. (Frontiers in Endocrinology, 2023)
The apelin receptor binds two distinct endogenous peptides, apelin and ELA, which act in an autocrine/paracrine manner to regulate the human cardiovascular system. As a class A GPCR, the apelin receptor is an attractive therapeutic target in cardiovascular disease. With improvements in imaging techniques, and the stability and brightness of dyes, fluorescent ligands are becoming increasingly more useful in studying protein targets. Here, we describe four novel fluorescent ligands; two based on [Pyr1]apelin-13 (apelin488 and apelin647), and two based on ELA-14 (ELA488 and ELA647). All four ligands retained their ability to bind and activate the apelin receptor as agonists and, crucially, triggered receptor internalisation. Apelin647 was validated in cell-based platforms using high content imaging, and showed suitability as a safer and more high-throughput alternative to radiolabelled compounds, having potential for use in drug discovery pipelines. Apelin647 was also used to qualitatively visualise and quantify apelin receptor internalisation. Further, apelin488 and ELA488 were used to visualise the expression and distribution of apelin receptor in blood vessels and tubules of the renal cortex. Our data indicate that the described novel fluorescent ligands expand the pharmacological toolbox for studying the apelin receptor.